The Value of Intraoperative Frozen Section Analysis for Margin Status in Breast Conservation Surgery in a Nontertiary Institution. (30th September 2014) - Tan, Mona P.; Sitoh, Nadya Y.; Sim, Amanda S.
Abstract : Introduction . Breast conservation treatment (BCT) for early-stage breast malignancies requires negative margins and good cosmesis. Reoperations may be needed to achieve negative margins, which can have an adverse impact on outcomes. This study was performed to evaluate the efficacy of intraoperative frozen section analysis (IFSA) for margin assessment to reduce excision rates. Methods . All patients treated at the authors' private healthcare facility between 2009 and 2011 for breast cancer were included in the study. Those for whom BCT was intended underwent wide excision with IFSA. Six margins of the excised tissue, and the sentinel lymph node (SLN), where appropriate, were submitted for IFSA. Patient demographics, tumour characteristics, number of operations performed, and outcomes were analysed. Results . Of the 161 patients analysed, 138 (85.7%) had successful breast conservation. Four patients required a reoperation for incomplete surgical extirpation. One had a false negative SLN assessment on IFSA, and was returned to the operating room for an axillary dissection. Three patients required reoperations for inadvertently missed multicentric disease. None had false negative margin evaluation with IFSA necessitating reexcision. Conclusion . The use of IFSA allows low rates of reoperation with BCT. Further research is needed to establish consistency in low reexcision rates for cost-effectiveness and optimum resource allocation.